Accurately Determining Labor Test Results Using the Rough Set Method - Retno Devita; Sarjon Defit (Jurnal Penelitian Pendidikan IPA, 2024)
An exam is something that must be done to test a person's ability or intelligence. The laboratory exam in the Computer Systems study program at Putra Indonesia University "YPTK" Padang consists of a digital systems exam, a fuzzy logic control exam, and a tool presentation. The Labor Exam must be passed by students who will take the comprehensive exam. In this study, laboratory exam data was taken for 20 students. So far, processing of student laboratory exam results has been done manually so it takes a long time to make decisions. To overcome this problem, a Rough Set method is used to determine laboratory test results. The Rough Set method is part of machine learning. This research produces 29 rules as knowledge, namely Digital System Or A = 3 rules, Fuzzy Logic Or B = 3 rules, Tool Presentation Or C = 3 rules, {Fuzzy Logic, Tool Percentage} Or BC = 6 rules, {Digital System, Fuzzy Logic} Or AB = 6 rules and {Digital System, Tool Percentage} Or AC = 8 rules. The Rough Set method can determine student laboratory exam results (pass or fail) accurately.